Motion stability criteria of a worker on floating solar modules - Lee, Hao Wei (Nanyang Technological University, 2022)
Singapore has pledged to quadruple solar energy deployment to 1.5 gigawatt-peak by 2025, with aims to do so by increasing R&D in this industry. Given the land scarcity faced by the small island nation, harnessing solar energy through on-land solar farms has proved to be an uphill task. As such, two floating solar farms have been test-bedded and built across various water bodies in the past two years. One of these include the newer offshore floating solar farm recently moored in place off the coast of Woodlands, in the Straits of Johor.